Bad boys for life [videorecording (DVD)] - Smith, Will, 1968-; Lawrence, Martin, 1965-; Hudgens, Vanessa, 1988-; Ludwig, Alexander, 1992- (Sony Pictures Home Entertainment, 2020)
Although he's set to retire and looking forward to it, Marcus agrees to help his old partner one last time to discover and stop whoever has been attempting to assassinate Mike. Now the "old guard", they work with a new division of hotshots on the Miami PD called AMMO -- and find themselves hunting the head of the Aretas Cartel.